Canonical Secretomes, Innate Immune Caspase-1-, 4/11-Gasdermin D Non-Canonical Secretomes and Exosomes May Contribute to Maintain Treg-Ness for Treg Immunosuppression, Tissue Repair and Modulate Anti-Tumor Immunity via ROS Pathways - Ni, Dong; Tang, TingTing; Lu, Yifan; Xu, Keman; Shao, Ying; Saaoud, Fatma; Saredy, Jason; Liu, Lu; Drummer, Charles; Sun, Yu; Hu, Wenhui; Lopez-Pastrana, Jahaira; et al. (Frontiers in Immunology, 2021)
We performed a transcriptomic analyses using the strategies we pioneered and made the following findings: 1) Normal lymphoid Tregs, diseased kidney Tregs, splenic Tregs from mice with injured muscle have 3, 17 and 3 specific (S-) pathways, respectively; 2) Tumor splenic Tregs share 12 pathways with tumor Tregs; tumor splenic Tregsand tumor Tregs have 11 and 8 S-pathways, respectively; 3) Normal and disease Tregs upregulate some of novel 2641 canonical secretomic genes (SGs) with 24 pathways, and tumor Tregs upregulate canonical secretomes with 17 pathways; 4) Normal and diseased tissue Tregs upregulate some of novel 6560 exosome SGs with 56 exosome SG pathways (ESP), tumor Treg ESP are more focused than other Tregs; 5) Normal, diseased and tumor Tregs upregulate some of novel 961 innate immune caspase-1 SGs and 1223 innate immune caspase-4 SGs to fulfill their tissue/SG-specific and shared functions; 6) Most tissue Treg transcriptomes are controlled by Foxp3; Tumor Tregs had increased Foxp3 non-collaboration genes with ROS and 17 other pathways; 7) immune checkpoint receptor PD-1 does, but CTLA-4 does not, play significant roles in promoting Treg upregulated genes in normal and diseased tissue Tregs; and tumor splenic and tumor Tregs have certain CTLA-4-, and PD-1-, non-collaboration transcriptomic changes with innate immune dominant pathways; 8) Tumor Tregs downregulate more immunometabolic and innate immune memory (trained immunity) metabolic genes than Tregs from other groups; and 11) ROS significantly regulate Treg transcriptomes; and ROS-suppressed genes are downregulated more in tumor Tregs than Tregs from other groups. Our results have provided novel insights on the roles of Tregs in normal, injuries, regeneration, tumor conditions and some of canonical and innate immune non-canonical secretomes via ROS-regualtory mechanisms and new therapeutic targets for immunosuppression, tissue repair, cardiovascular diseases, chronic kidney disease, autoimmune diseases, transplantation, and cancers.